Vascular Microsurgery (Multidisciplinarian Team). Case Report: casos clínicos - Irigaray, Alberto; Roncagliolo, Aldo (Cirugía del Uruguay, 1979)
Report of experience of Vascular Repair Microsurgery Team, with review of sone cases operated during 1978. These operations were partly performed in the Piastic Surgery Service of the Pasteur Hospital.